The Problem of Temporality in Phenomenological Psychiatry - Mikayelyan, Vladimir (Bulletin of Yerevan University E: Philosophy, Psychology, 2018)
If the psychological analysis becomes the subject of a scientific analysis, then, in this case, we will not advance even a single step, guided by the causal principle of treating psychic phenomena. For a person, the predictability of both the surrounding world and himself is of particular value. The ability to explain is ultimately the ability to live. The world of man and the world outside of man must have concrete interpretational models. Everything that fits into the cause-and-effect scheme is for us the ultimate truth. Therefore, it is inherent in man to constantly maintain and nourish the myth of the causality of all that exists.